2020
DOI: 10.1002/bies.202000037
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Ancestor of all Eukaryotes: A Defense of the “Meiosis Toolkit”

Abstract: The distribution pattern of the meiotic machinery in known eukaryotes is most parsimoniously explained by the hypothesis that all eukaryotes are ancestrally sexual. However, this assumption is questioned by preliminary results, in culture conditions. These suggested that Acanthamoeba, an organism considered to be largely asexual, constitutively expresses meiosis genes nevertheless—at least in the lab. This apparent disconnect between the “meiosis toolkit” and sexual processes in Acanthamoeba led to the conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 136 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…Meiosis is a key process in evolutionary diversification in eukaryotic organisms, however in several groups of green algae, sexual reproduction is either absent or yet undocumented, as appears to be the case for most planktonic species [1,113]. The presence of core meiotic determinant genes (though many more are involved in the process) [114,115] was examined to assess whether P. SENEW3 is likely to undertake sexual reproduction. Several of these were identified: DMC1, HOP2, MSH5 (and homologues MSH2 and MSH6) SPO11-2, HAP2 and MER3; yet six others were missing (Table S13), suggesting but leaving uncertain whether P. SENEW3 can undergo meiosis.…”
Section: Gene Contentmentioning
confidence: 99%
“…Meiosis is a key process in evolutionary diversification in eukaryotic organisms, however in several groups of green algae, sexual reproduction is either absent or yet undocumented, as appears to be the case for most planktonic species [1,113]. The presence of core meiotic determinant genes (though many more are involved in the process) [114,115] was examined to assess whether P. SENEW3 is likely to undertake sexual reproduction. Several of these were identified: DMC1, HOP2, MSH5 (and homologues MSH2 and MSH6) SPO11-2, HAP2 and MER3; yet six others were missing (Table S13), suggesting but leaving uncertain whether P. SENEW3 can undergo meiosis.…”
Section: Gene Contentmentioning
confidence: 99%
“…At present, caution is required defining cell types based solely on their morphology, given that few molecular markers are available to identify life cycle forms [35,38,46,47]. The shape and configuration of the Leishmania cell are nevertheless linked intimately with the pathogenicity and ecological niche of the species, and must be transmitted accurately from one generation to the next during mitotic division, although recent studies have shown meiosis-like sexual recombination in Leishmania, and other sexual processes may be possible [22,41,[48][49][50]. Both forms of development conserve their basic cell architecture and ultrastructural features over the course of the life cycle, with the kinetoplast anterior to the nucleus [44,45,47,49,50].…”
Section: Leishmanine Trypanosomatids Are Unicellular Organisms and Excellent Models To Explain Microbial Virulencementioning
confidence: 99%
“…The shape and configuration of the Leishmania cell are nevertheless linked intimately with the pathogenicity and ecological niche of the species, and must be transmitted accurately from one generation to the next during mitotic division, although recent studies have shown meiosis-like sexual recombination in Leishmania, and other sexual processes may be possible [22,41,[48][49][50]. Both forms of development conserve their basic cell architecture and ultrastructural features over the course of the life cycle, with the kinetoplast anterior to the nucleus [44,45,47,49,50]. In these cells, much of the single, branched mitochondrion contains kinetoplast DNA (kDNA) that is connected to the basal body, where a single flagellum extends from the flagellar pocket (FP), to which it is attached by a cytoskeletal structure called the Flagellum Attachment Zone (FAZ) (Figure 3) [40,41,[44][45][46].…”
Section: Leishmanine Trypanosomatids Are Unicellular Organisms and Excellent Models To Explain Microbial Virulencementioning
confidence: 99%
“…Moreover, genomic approaches proved to be powerful for identifying other specific eukaryotic features such as meiosis (a stage of sexual reproduction), which evolved early in eukaryotes (Speijer et al 2015) and for which a full set of responsible genes was proposed, mostly defined from Opistokonta and plants. Using the proposed meiosistoolkit, it has been possible to perform large-scale comparative analysis and search for these genes in other protists like diatoms (Ramesh et al 2005, Malik et al 2008, Patil et al 2015, Hofstatter et al 2020. Similarly, genomics supported the discovery of flagellum specific proteins (flagellum toolkit) in Opistokonta (Torruella et al 2015) or Fungi , helping to elucidate the evolutionary history of this ancestral feature specific of a given lifestyle.…”
Section: 22-answers From Genomicsmentioning
confidence: 99%